Effects of yeast strain on anthocyanin, color, and antioxidant activity of mulberry wines. Issue 6 (7th August 2017) - Liu, Shujing; Wu, Caie; Fan, Gongjian; Li, Tingting; Ying, Ruifeng; Miao, Yun
Abstract: In this study, the effects of yeast strains on anthocyanin, color, and antioxidant activity of mulberry wines were investigated. Principal component analysis (PCA) were used to evaluate differences among the five mulberry wines. Results showed that yeast strains have a significant effect on anthocyanin, color, and antioxidant activity of mulberry wines. The total phenol content in mulberry wines were 145.42–197.65 mg gallic acid equivalents/100 mL. Cyanidin‐3‐O‐glucoside (C3G) and cyanidin‐3‐O‐rutinoside (C3R) were two major anthocyanins in mulberry wine. The C3G contents ranged from 3.56 to 7.69 mg/100 mL, while C3R ranged from 4.28 to 8.38 mg/100 mL. Total phenol content, total flavonoids content and antioxidant activity in mulberry wine fermented by yeast SY were significantly higher ( p < .05) than the other wines. Two principal components accounted for 88.31% of total variance. Results of PCA indicated that these five mulberry wines could differentiated by anthocyanin, color, and antioxidant activity. Practical applications: This study was undertaken, in order to further examine the effects of different yeast strains on the anthocyanin, color, and antioxidant activity of mulberry wines. An appropriate yeast strain may help reducing anthocyanin degradation in mulberry wine during fermentation, avoiding a dramatic impact on its color and protecting the beneficial effects of these biologically active compounds on human health. Finally, mulberry wines will provide a new perspective for winemakers and will become alternative functional food for health‐conscious consumers in the future.